Augmented reality marketing in Malaysia—future scenarios - Choon, Ching Ng; Ramasamy, Chandrashekar (MDPI, 2018)
Augmented Reality (AR) marketing is a novel and creative way to market products and services. However, there are concerns about its marketing effectiveness as it is still immature to take over the place of traditional marketing method. Hence, this study was aimed to identify the issues and drivers of employing AR, in marketing, and to study the future trend of AR marketing in Malaysia. Foresight methodology tool, the Social, Technological, Environmental, Economic, Political, and Values (STEEPV) method was used in identifying the issues and drivers of employing AR in marketing. Furthermore, an impact–uncertainty analysis was used to identify the top two drivers of the subject. The top two drivers identified were the “need for interrelation between the virtual and the real word” and “technological knowledge generation” with the highest statistical mean vote for impact and uncertainty, respectively. The development of scenario analysis was constructed in correspondence with the top two drivers which gave insights into the four alternative possibilities in the time horizon of 5 to 10 years. The drivers must coexist in order to generate potential scenarios for the development and sustainability of AR marketing in Malaysia.